Flowered Grain Quality and Phytochemical Content of Non-Conventional Maize Hybrids from the Mexican Subtropics across Three Growing Cycles - Leticia García-Cruz; María Gricelda Vázquez-Carrillo; Ricardo Ernesto Preciado-Ortiz (Plants, 2023)
Development of non-conventional hybrids responds to the demand for the Elotes Occidentales land-race for production of pozole. The effect of growing cycle (2019, 2020, and 2021) on physical characteristics, flowered grain quality, and phytochemical content of two non-conventional hybrids of pozolero maize, as well as the effect of the presence or absence of pedicel, type of pollination (open and controlled, 2019), and parents (female and male, 2020) on flowered grain quality and content of phytochemical compounds, were evaluated. Size, hardness, color, total phenols, and anthocyanins in unprocessed grain were determined. Yield, volume, and puncture force were measured in flowered grain. Results were analyzed with a factorial arrangement in a completely randomized design. There were significant differences (p ≤ 0.05) in most of the variables studied by effect of crop cycle and hybrid. Non-conventional hybrids had large grains (40 g 100 grains−1), soft endosperm (flotation index > 60), pink-purple color, and phenol and anthocyanin contents similar to those reported for the Elotes Occidentales land-race. The presence or absence of the pedicel did not affect flowered grain quality. Controlled pollination favored anthocyanin synthesis. The female parent determined the anthocyanin content of non-conventional hybrids. Thermal processing reduced anthocyanins by 60%; however, they leached into the flowering broth, so that the pozole made from non-conventional hybrids can have improved nutraceutical value, relative to that of pozole made with Cacahuacintle land-race.